2018
DOI: 10.1093/aje/kwy185
|View full text |Cite
|
Sign up to set email alerts
|

Invited Commentary: Detecting Individual and Global Horizontal Pleiotropy in Mendelian Randomization—A Job for the Humble Heterogeneity Statistic?

Abstract: Mendelian randomization (MR) is gaining in recognition and popularity as a method for strengthening causal inference in epidemiology by utilizing genetic variants as instrumental variables. Concurrently with the explosion in empirical MR studies, there has been the steady production of new approaches for MR analysis. The recently proposed “global and individual tests for direct effects” (GLIDE) approach fits into a family of methods that aim to detect horizontal pleiotropy—at the individual single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
157
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 27 publications
0
157
0
Order By: Relevance
“…We also tested whether the Egger intercept is significantly different from zero as a measure of unbalanced pleiotropy or violation of the InSIDE assumption (59). Furthermore, heterogeneity amongst the IV ratio estimates was quantified using Cochran's Q statistic, given that horizontal pleiotropy may be one explanation for significant heterogeneity (44,60,61). A global pleiotropy test was implemented via the MR-PRESSO framework utilising the expected and observed RSS (56).…”
Section: Sensitivity and Pleiotropy Analysesmentioning
confidence: 99%
“…We also tested whether the Egger intercept is significantly different from zero as a measure of unbalanced pleiotropy or violation of the InSIDE assumption (59). Furthermore, heterogeneity amongst the IV ratio estimates was quantified using Cochran's Q statistic, given that horizontal pleiotropy may be one explanation for significant heterogeneity (44,60,61). A global pleiotropy test was implemented via the MR-PRESSO framework utilising the expected and observed RSS (56).…”
Section: Sensitivity and Pleiotropy Analysesmentioning
confidence: 99%
“…Full details are provided elsewhere 15 , but briefly, we used the so-called 'modified 2 nd order weighting' approach to estimate total Cochran's Q statistic as a measure of heterogeneity, as well as the individual contributions of each SNP, q i 15 . This has been shown to be comparable to the simulationbased approach in MR-PRESSO, providing a well-calibrated test statistic for outlier status whilst being computationally more efficient 14,20 . The probability of a SNP being an outlier is calculated based on q i being chi-square distributed with 1 degree of freedom.…”
Section: Outlier Detectionmentioning
confidence: 90%
“…MR analyses based on single SNPs suggested that both SNPs contributed to the overall causal effects we observed (Supplementary Table 6). Heterogeneity analysis of the instruments suggested that causal estimates were consistent across both SNPs (P values of Cochran Q test > 0.05), with the exception of estimates for lumbar spine BMD and fracture risk, likely reflecting the lower power in these instances (44). Genetic signals for sclerostin and eBMD colocalized at both the B4GALNT3 locus (PP=99.7%) and GALNT1 locus (PP=99.8%) ( Supplementary Table 7), further strengthening the evidence of the putative causal relationship between sclerostin and eBMD.…”
Section: Mendelian Randomization and Colocalization Analysis Of Sclermentioning
confidence: 99%